2007
DOI: 10.1177/1541204007300358
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Serious Violence

Abstract: Applying insights from social influence literature, in combination with key elements of gender organization and socialization, the effect of friendship sex composition and exposure to peer violence on girls' and boys' involvement in serious violence is examined. It is hypothesized that the impact of opposite-sex friendships on violence will differ for female youth compared to male youth. The exceptionally detailed friendship network data available in the Add Health for a sample of adolescents (N = 14,044) is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…Net of these controls, and based on previous research on adult supervision (Greene & Banerjee, 2009; Osgood et al, 1996; Pettit et al, 1999) and peer group gender composition (Arndorfer & Stormshak, 2008; Haynie, et al, 2007; Richards et al, 1998), we expected unsupervised time, particularly time with mixed/opposite sex peers, to negatively predict, and supervised time, particularly time with mixed/opposite sex peers, to positively predict youth adjustment. We also examined potential gender differences in the implications of peer involvement and tested for interactions between time with peers and youths’ gender, but proposed no specific hypotheses, given that gender differences in peer influences have been documented in some studies (Haynie et al, 2007; Mrug et al, 2011), but not others (Arndorfer & Stormshak, 2008; Battin-Pearson et al, 2000; Fergusson et al, 2003; Fuligni et al, 2001).…”
Section: Adjustment Correlates Of Time With Peersmentioning
confidence: 99%
See 3 more Smart Citations
“…Net of these controls, and based on previous research on adult supervision (Greene & Banerjee, 2009; Osgood et al, 1996; Pettit et al, 1999) and peer group gender composition (Arndorfer & Stormshak, 2008; Haynie, et al, 2007; Richards et al, 1998), we expected unsupervised time, particularly time with mixed/opposite sex peers, to negatively predict, and supervised time, particularly time with mixed/opposite sex peers, to positively predict youth adjustment. We also examined potential gender differences in the implications of peer involvement and tested for interactions between time with peers and youths’ gender, but proposed no specific hypotheses, given that gender differences in peer influences have been documented in some studies (Haynie et al, 2007; Mrug et al, 2011), but not others (Arndorfer & Stormshak, 2008; Battin-Pearson et al, 2000; Fergusson et al, 2003; Fuligni et al, 2001).…”
Section: Adjustment Correlates Of Time With Peersmentioning
confidence: 99%
“…However, the focus of these studies was on peer group structure rather than on peer group involvement. Further, the reliance on youths’ self-reports to measure friendship networks means that the results might be subject to perception bias (Haynie, Steffensmeier, & Bell, 2007) and recency or primacy effects (Eagle, Pentland, & Lazer, 2009). …”
Section: Developmental Course Of Time With Peersmentioning
confidence: 99%
See 2 more Smart Citations
“…Haynie, Steffensmeier, and Bell (2007) found that exposure to opposite-gender friends increased females' odds of engaging in serious violence and reduced males' involvement in serious violence. In addition, as the proportion of opposite-gender friends increased in girls' friendship networks, peer influence increased.…”
Section: Interpersonal Relationships: Gendered Nature Of Girls' Delinmentioning
confidence: 98%